2007
DOI: 10.1093/jn/137.3.652
|View full text |Cite
|
Sign up to set email alerts
|

Dietary l-Arginine Supplementation Enhances the Reproductive Performance of Gilts

Abstract: Arginine is a common substrate for the synthesis of nitric oxide and polyamines that are crucial for placental angiogenesis and growth in mammals. This study was conducted to test the hypothesis that dietary l-arginine supplementation may improve reproductive performance of pregnant gilts. Fifty-two pregnant gilts with body weight (BW) of 166.3 +/- 1.8 kg were housed individually in gestation crates. At d 30 of gestation, gilts were assigned randomly to corn-soybean-based diets supplemented with 1.0% L-arginin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
204
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(233 citation statements)
references
References 37 publications
14
204
4
2
Order By: Relevance
“…This study utilized multiparous sow to better comprehend the status of oxidative stress during different stages of reproduction. The performance of all sows in this study was normal, which is similar to our previous publications, with regard to BW gain during gestation, BW changes during lactation, feed intake during gestation and lactation, litter size, litter birth weight and litter weight gain (Mateo et al, 2007(Mateo et al, , 2008(Mateo et al, and 2009Kim et al, 2009). In this study, there was no truly non-pregnant sow to compare the oxidative damage with pregnant sow because of practical difficulty in obtaining non-pregnant sows with similar age, parity and BW to those used in this study.…”
Section: Discussionsupporting
confidence: 90%
“…This study utilized multiparous sow to better comprehend the status of oxidative stress during different stages of reproduction. The performance of all sows in this study was normal, which is similar to our previous publications, with regard to BW gain during gestation, BW changes during lactation, feed intake during gestation and lactation, litter size, litter birth weight and litter weight gain (Mateo et al, 2007(Mateo et al, , 2008(Mateo et al, and 2009Kim et al, 2009). In this study, there was no truly non-pregnant sow to compare the oxidative damage with pregnant sow because of practical difficulty in obtaining non-pregnant sows with similar age, parity and BW to those used in this study.…”
Section: Discussionsupporting
confidence: 90%
“…By excluding the early gestation period, dietary Arg supplementation starting from day 22 or 30 of gestation and continuing until farrowing markedly improved placental growth and litter performance (Mateo et al, 2007;Gao et al, 2012). In this study, Arg supplemented to sows from day 30 to day 90 (Arg90 group) or 114 of gestation (Arg114 group) did not markedly increase total pigs born, however, the less dead pigs in sows receiving Arg between days 30-114 of gestation resulted in more live-born pigs, compared with sows with no Arg supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…putrescine, spermidine, and spermine), which are crucial for placental angiogenesis, trophoblast growth, and uteroplacental blood flow, thereby stimulating nutrients transfer and wastes exchange, consequently fetal growth and development (Wu et al, 2006). It has been reported that dietary Arg supplementation from early gestation until day 114 of gestation enhanced sow placental growth, litter size, and weight (Mateo et al, 2007;Gao et al, 2012). However, the sow placental growth has reached maximum in late gestation (McPherson et al, 2004;Freking et al, 2007), instead the efficient placenta in late gestation is physiologically required for rapid fetal growth in the last 20 days of gestation (Biensen et al, 1999;Macpherson et al, 2004).…”
mentioning
confidence: 99%
“…Therefore, nutrient partitioning among fetuses is less variable as is within-litter variation in birth weight of piglets. However, there are other reports that do not indicate positive effects of dietary supplementation with L-arginine during mid-gestation to term on within-litter uniformity (Mateo et al, 2007;Gao et al, 2012). These different findings may be explained by differences in the total amounts of dietary L-arginine and other amino acids consumed by gestating pigs (Wu et al, 2013b;2013c).…”
Section: Nutrition Related To Fetal Growth During Late Gestationmentioning
confidence: 96%
“…Amino acids in the arginine family (arginine, glutamine, glutamate, proline, aspartate, asparagine, citrulline, and ornithine) have been studied extensively given their prominent effects in improving litter size (Greenberg et al, 1997;Hazeleger et al, 2007;Mateo et al, 2007;Gao et al, 2012;Li et al, 2014). At the same time, dietary supplementation with 25.5 g/d L-arginine from Day 77 of pregnancy until term reduced within-litter variation in birth weight of live-born piglets by 20.6% and 25.4% in arginine and control groups, respectively (Quesnel et al, 2014).…”
Section: Nutrition Related To Fetal Growth During Late Gestationmentioning
confidence: 99%